Characterization of the Relationship of Inotuzumab Ozogamicin Exposure With Efficacy and Safety End Points in Adults With Relapsed or Refractory Acute Lymphoblastic Leukemia - Joseph Chen; May Haughey; Erik Vandendries; Daniel J. DeAngelo; Hagop M. Kantarjian; Ana Ruiz‐Garcia (Wiley, 2021)
Inotuzumab ozogamicin (InO), an anti‐CD22 monoclonal antibody conjugated to calicheamicin, is approved in Europe and the United States for treatment of adults with relapsed or refractory acute lymphoblastic leukemia (ALL). Population analyses were performed to evaluate the relationship between InO exposure and efficacy and safety end points in patients with ALL. The probability of achieving complete remission/complete remission with incomplete hematologic recovery (CR/CRi) and minimal residual disease (MRD)‐negativity for InO relative to chemotherapy was also investigated. Data from study 1010 (NCT01363297) and INO‐VATE (NCT01564784) were pooled for exposure-response (InO, n = 234) and treatment-response (InO, n = 234; chemotherapy, n = 143) analyses. The analyses demonstrated that InO exposure was significantly correlated with achieving CR/CRi and MRD‐negativity, as well as with hepatic event adjudication board‐reported veno‐occlusive disease/sinusoidal obstruction. Patients with ALL treated with InO had significantly greater odds of achieving CR/CRi (7‐times higher) and MRD‐negativity (13‐times higher) than those receiving chemotherapy.